Transformation and Sustainability of Livelihoods in Muslim Families - Yasin, Ahmad Alamuddin; Salikin, Adang Djumhur; Jaelani, Aan; Setyawan, Edy (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
From the perspective of classical scholars, the only things that constitute a livelihood are clothes, food, and lodging. According to traditional scholars, the husband is not responsible for taking care of the family's health, education, or any essential needs except clothing, food, and shelter. Wives frequently demand goods that are not even primary needs, which causes complications. The implementation of a living is not in accordance with the notions of classical fiqh since of course how individuals see how to provide for themselves has changed through time. The implementation of maintenance in Islamic families in Indonesia and the causes that cause different maintenance implementations will be the main topics of this study. Therefore, this study aims to analyze the transformation of livelihood in Muslim families. Multiple case studies, also known as collective case studies, are used in this study. Primary and secondary data sources were used to gather the data. Data reduction, data presentation, and data verification were used in the data analysis process. According to the study's findings, although life was once thought of as a gift a husband gave to his wife and only addressed a few basic necessities, it is no longer the same. The findings of this study offer a notion of five changes in livelihood. Specifically, transformation and continuation of the definition of subsistence, transformation and continuation of subsistence customs, transformation and continuation of subsistence forms, and transformation and continuation of subsistence processes.